Thermospermine Synthase (ACL5) and Diamine Oxidase (DAO) Expression Is Needed for Zygotic Embryogenesis and Vascular Development in Scots Pine - Vuosku, Jaana; Muilu-Mäkelä, Riina; Avia, Komlan; Suokas, Marko; Kestilä, Johanna; Läärä, Esa; Häggman, Hely; Savolainen, Outi; Sarjala, Tytti (Frontiers in Plant Science, 2019)
Unlike in flowering plants, the detailed roles of the enzymes in the polyamine (PA) pathway in conifers are poorly known. We explored the sequence conservation of the PA biosynthetic genes and diamine oxidase (DAO) in conifers and flowering plants to reveal the potential functional diversification of the enzymes between the plant lineages. The expression of the genes showing different selective constraints was studied in Scots pine zygotic embryogenesis and early seedling development. We found that the arginine decarboxylase (ADC) pathway is strongly preferred in putrescine production in the Scots pine as well as generally in conifers and that the reduced use of ornithine decarboxylase (ODC) has led to relaxed purifying selection in ODC genes. Thermospermine synthase (ACL5) genes evolve under strong purifying selection in conifers and the DAO gene is also highly conserved in pines. In developing Scots pine seeds, the expression of both ACL5 and DAO increased as embryogenesis proceeded. Strong ACL5 expression was present in the procambial cells of the embryo and in the megagametophyte cells destined to die via morphologically necrotic cell death. Thus, the high sequence conservation of ACL5 genes in conifers may indicate the necessity of ACL5 for both embryogenesis and vascular development. Moreover, the result suggests the involvement of ACL5 in morphologically necrotic cell death and supports the view of the genetic regulation of necrosis in Scots pine embryogenesis and in plant development. DAO transcripts were located close to the cell walls and between the walls of adjacent cells in Scots pine zygotic embryos and in the roots of young seedlings. We propose that DAO, in addition to the role in Put oxidation for providing H2O2 during the cell-wall structural processes, may also participate in cell-to-cell communication at the mRNA level. To conclude, our findings indicate that the PA pathway of Scots pines possesses several special functional characteristics which differ from those of flowering plants.